Interrater-Reliabilität der OPD-KJ-Achsen Konflikt und Struktur - Stefini, Annette; Reich, Günter; Horn, Hildegard; Winkelmann, Klaus; Ohmes, Ursula; Frost, Ulrike; Kronmüller, Klaus-Thomas (Praxis der Kinderpsychologie und Kinderpsychiatrie, 2013)
Summary Interrater-Reliability of the OPD-CA, the Axes Conflict and Structure The reliability of the meanwhile widely used Operationalized Psychodynamic Diagnostics in childhood and adolescence (OPD-CA) is only rarely examined. By means of audiovisual recordings of OPD-CA-interviews with 39 adolescents in the context of a randomized-controlled psychotherapy study for the treatment female adolescents with bulimia nervosa and atypical bulimia nervosa the reliability of the axis conflict and the axis structure were examined. This was carried out by the calculation of Intraklassen-correlations of three raters. The rater agreements ranged from good to excellent, except for impulse control in the axis structure, where the results were satisfactory. The relevance of the results for clinical practice is discussed.